PENERAPAN TEKNIK DICTOGLOSS DAN MINDMAP DALAM MENINGKATKAN KETERAMPILAN MENYIMAK SISWA KELAS IV-B SDN PADASUKA I PADA MATERI PENGUMUMAN - Margana, Denais Palestin; Iswara, Prana Dwija; Gusrayani, Diah (Jurnal Pena Ilmiah, 2017)
The result of learning listening an announcement that held in grade IV in SDN Padasuka I are still low. This can be seen in their study result in listening an announcement. The students are hard to listen to the announcement so the students can’t retell the announcement. So, to fix this problem, the dictogloss and mindmap are used. The method that used in this research is classroom action research by Kemmis and Mc. Taggart that has four steps.To improve teacher performance, student activity, and the study result. The result in every cycle are increasing. In cycle I, there are 7 or 33% student who pass the test, In cycle II, there are 13 or 62% student who pass the test, In cycle III, there are 18 or 86% student who pass the test. Thus, through the application of dictogloss and mindmap can improve student learning outcomes in the material announcement.